Blog theory : feedback and capture in the circuits of drive - Dean, Jodi, 1962- (Cambridge : Polity, 2010)
Blog Theory offers a critical theory of contemporary media. Furthering her account of communicative capitalism, Jodi Dean explores the ways new media practices like blogging and texting capture their users in intensive networks of enjoyment, production, and surveillance.
Includes bibliographical references and index.
boek